Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Transportasi Yang Terdaftar Di Bursa Efek Indonesia - Putri, Juwita Aulia Deswita; Linawati , Linawati; Solikah, Mar’atus (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research aims to determine whether there is an influence between company size, liquidity, debt policy and tax planning on company value partially and simultaneously in transportation companies listed on the BEI for the 2020-2023 period. This research uses a quantitative causal comparative method. The sample in this research used a purposive sampling method and obtained 13 companies. This research uses secondary data. The analysis technique in this research uses multiple linear regression analysis techniques. The results of this study show that company size, liquidity and debt policy partially have a significant effect on company value, while tax planning partially has no significant effect on company value. Simultaneously company size. liquidity, debt policy and tax planning have a significant effect on company value.